(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Digital Substraction Angiography (DSA) is the gold standard for proper diagnosis and further evaluation of intra cranial aneurysm. Intracranial aneurysm rupture leading to Subarachnoid hemorrhage (SAH) may be associated with serious neurological sequelae or even mortality. According to international literature, only aneurysm >7 mm or aneurysm in the posterior circulation require treatment. Retrospective single center studies have however, disputed that the average size of ruptured aneurysms are <7 mm. Objective: To assess the aneurysm characteristics and demographics of patients who reported to CMH, Dhaka with SAH secondary to an aneurysm detected at Digital Subtraction Angiography (DSA). Materials and Methods: This retrospective study was conducted among the patients who presented with SAH more than 3 year period, from November 2013 to April 2017. All patients had undergone CT scan of brain in the department of Radiology & Imaging and DSA in the Cath Lab of Combined Military Hospital (CMH), Dhaka. Data about aneurysm characteristics, size and patient demographics were obtained from patients files. Results: A total of 74 patients underwent DSA and amongst them 32 patients had ruptured aneurysms. Ages ranging from 20 to 75 years (mean 45 years), little more male patients. The mean size of aneurysms was 5.8mm (range 1.2 mm to 20 mm) with 74.5% of aneurysms having size <7 mm. Most aneurysms were noted involving anterior circulation (72%) with the majority arising from the anterior communicating (ACom) artery (36.7%). Conclusion: An aneurysm is an abnormal dilatation of an artery. It can be found in almost any age and can rupture at size <7 mm. Those are commonly located in the anterior circulation. Findings of this study emphasize the importance of conducting the institutional reviews, to consider adapting the international treatment guidelines. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 107-110